2014
DOI: 10.1167/iovs.14-14439
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Thickness in Unilateral Amblyopic Children

Abstract: In the subfoveal area, the choroid was thicker in amblyopic eyes than in fellow eyes in children with amblyopia. Furthermore, differences were found in the choroidal thickness in both eyes of children with amblyopia compared with participants with normal vision. A thicker choroid is somehow related to amblyopia, and this may be a useful diagnostic parameter for amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…However, other studies, including our study, show that CT of hypermetropic anisometropic amblyopic eyes is thick, even when the difference in the AL or refractive error between amblyopic and fellow eyes is taken into account in the statistical analysis [10, 12, 19]. Furthermore, other investigations have reported changes in the profile of CT [20], in the choroidal structure [21], and in the choroidal blood flow [13] exist in hypermetropic anisometropic amblyopic eyes.…”
Section: Discussionmentioning
confidence: 70%
“…However, other studies, including our study, show that CT of hypermetropic anisometropic amblyopic eyes is thick, even when the difference in the AL or refractive error between amblyopic and fellow eyes is taken into account in the statistical analysis [10, 12, 19]. Furthermore, other investigations have reported changes in the profile of CT [20], in the choroidal structure [21], and in the choroidal blood flow [13] exist in hypermetropic anisometropic amblyopic eyes.…”
Section: Discussionmentioning
confidence: 70%
“…[26][27][28] Nishi and colleagues 26 compared choroidal thickness of the amlyopic eyes with fellow eyes and control eyes in a cohort of 25 patients with hyperopic anisometropic amblyopia and found that subfoveal choroidal thickness was 351.3 AE 54.7 mm in the amblyopic eyes, 283.5 AE 55.2 mm in the fellow eyes, and 282.7 AE 73.3 mm in the control eyes. However, only hyperopic anisometropic amblyopia patients were included in their study.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first analysis of amblyopic CC atrophy using SSADA‐OCT noninvasively, and the authors speculate that CC atrophy induced malfunction of the outer retina, resulting in an increase in SFCT. Similarly, Xu J et al found that amblyopic eyes had a greater choroidal thickness at and 2 mm nasal to the fovea compared with the fellow eyes of the children with amblyopia. Moreover, SFCT was moderately and negatively correlated with BCVA, which is inconsistent with the findings of Xu J et al .…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Xu J et al found that amblyopic eyes had a greater choroidal thickness at and 2 mm nasal to the fovea compared with the fellow eyes of the children with amblyopia. Moreover, SFCT was moderately and negatively correlated with BCVA, which is inconsistent with the findings of Xu J et al .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation